Determination of Earthquake Design Ratio for Fixed Offshore Platform Due to Aceh Earthquake in Malaysia - Saffuan, Wan Ahmad; A., Adnan; R., Nazir; Noram Irwan, Ramli; Mohamad Idris, Ali; M. Z., Ramli; Khairunisa, Muthusamy (Penerbit UMP, 2017)
The level of concern among civil engineers in Malaysia about the aspect to design the structural for earthquake design criteria is low. But there are some cities or countries occur earthquake very often such as Aceh, Indonesia. Actually the tremors happened in Malaysia region due to Aceh earthquake and it also affected fixed offshore structure in Malaysia which not all of the offshore structure in Malaysia designed to resist seismic loading. The objective of this study is to determine the earthquake design ratio for fixed offshore platform due to Aceh earthquake in Malaysia. All the environmental factors data are given such as ranges of wave height and ground motion acceleration. The environmental loadings such as wave and wind load have been designed by referring API (American Petroleum Institute) design criteria. There were three types of analysis had been carried out which were Free vibration analysis, Response spectrum analysis and Time history analysis. For the Response spectrum analysis, the analysis performed by using response spectra curves of EuroCode8. Time history analysis has been performed by referring to time history of earthquake in Aceh 2004. The computer software offshore platform were very stable when hit by the earthquake. It can be conclude that different design ratio gain from the analysis and most of the part of the structure were in good performance and condition.